2008
DOI: 10.1099/jmm.0.2008/001305-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential glycosaminoglycan binding of Chlamydia trachomatis OmcB protein from serovars E and LGV

Abstract: We recently showed that OmcB protein from Chlamydia trachomatis serovar LGV1 functions as an adhesin. In this study, we produced Escherichia coli expressing OmcB from serovar E and compared this OmcB to OmcB from serovar LGV1. Infectivity inhibition assays carried out with serovars LGV1 and E of C. trachomatis in the presence of recombinant OmcB showed considerable (~60 %) inhibition of infectivity. In the presence of heparan sulphate, there was significant inhibition (68 %) of adherence of E. coli expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…That would also explain why prior exposure to soluble heparin, which is highly sulfated, does not reduce adhesion of C. trachomatis serovar E EBs (13,14,18,19,30,31). Moreover, even heparan sulfate with its heterogeneous and reduced sulfate pattern is unable to block adhesion of C. trachomatis OmcB-E-presenting E. coli cells (32). In contrast, infection by C. trachomatis serovar L2 was inhibited only by the antibody RB4EA12, which recognizes N-sulfated, N-acetylated, and 6-Osulfated regions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That would also explain why prior exposure to soluble heparin, which is highly sulfated, does not reduce adhesion of C. trachomatis serovar E EBs (13,14,18,19,30,31). Moreover, even heparan sulfate with its heterogeneous and reduced sulfate pattern is unable to block adhesion of C. trachomatis OmcB-E-presenting E. coli cells (32). In contrast, infection by C. trachomatis serovar L2 was inhibited only by the antibody RB4EA12, which recognizes N-sulfated, N-acetylated, and 6-Osulfated regions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3A). However, three of them lie immediately C terminal to the single heparin-binding motif (amino acid [aa] 66 to 71; here referred to as the variable domain), and the residues at these positions very likely determine the serovar-specific difference in the heparin dependence of adhesion seen between OmcB proteins from the LGV (OmcB-L) and E (OmcB-E) serovars (12,13,32). Indeed, it has previously been shown that exchange of the variable amino acid at position 66 abrogates the heparin dependency of adhesion by serovar L1 OmcB and, conversely, induces partial heparin dependency of cell binding by serovar E OmcB (13).…”
mentioning
confidence: 99%
“…Furthermore, FGF2 enhances binding of Chlamydia in an heparan sulfate proteoglycan-dependent manner (37). Candidate Chlamydia proteins involved in these interactions include the Chlamydia OmcB protein, which binds to glycosaminoglycans, such as heparan sulfate (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…LGVl and E show GAG-dependent and independent binding to host cells, respectively, indicating that it may be involved in either the primary or secondary attachment step [114]. C. pneumoniae Pmp proteins contain tetrapeptide repeat motifs that mediate binding to epithelial cells, and a recent study indicates that the presence of multiple Pmps have an additive effect on attachment to host cells [115].…”
Section: Type III Secretionmentioning
confidence: 99%
“…LGVI but not E prevents EBs from binding [114] host cells. [111 ] mAb reduces C.trachomatis L2 binding.…”
Section: L2mentioning
confidence: 99%